N‐butylphthalide (NBP) ameliorated ischemia/reperfusion‐induced skeletal muscle injury in male mice via activating Sirt1/Nrf2 signaling pathway - Peng Lu; Wei‐Peng Li; Ben‐Jun Zhou; Wen‐Ze Tian; Xiang Lu; Wei Gao (Physiological Reports)
Abstract N‐butylphthalide (NBP) has been reported to have potential protective effects in ischemic stroke via its antioxidative properties. The present study was aimed to investigate the protective effects of NBP on ischemia/reperfusion (I/R)‐induced skeletal muscle injury. Mouse model of I/R‐induced skeletal muscle injury and hypoxia/reoxygenation (H/R)‐induced C2C12 myotube injury model were constructed to test the protective effects of NBP both in vivo and in vitro. Our results showed that I/R resulted in skeletal muscle injury, as evidenced by elevated levels of LDH, CK, ROS, 3‐NT, MDA, and 4‐HNE as well as decreased activities of SOD, GSH‐Px, and decreased expression of Myog and MyoD in gastrocnemius muscle, which was ameliorated by NBP treatment. Mechanistically, NBP treatment increased the expression of Sirt1 and Nrf2 in the injured skeletal muscle. Notably, the protective effects of NBP on I/R‐induced skeletal muscle injury was diminished by the treatment of Sirt1 inhibitor. Further studies in H/R‐induced C2C12 myotubes injury model also showed that NBP activated the Sirt1/Nrf2 pathway. NBP treatment upregulated the expression of myog and MyoD in H/R‐stimulated C2C12 myotubes, which was eliminated by silencing of Sirt1. Taken together, our results suggest that NBP may alleviated I/R‐induced skeletal muscle injury by activating Sirt1/Nrf2 signaling pathway.